Mean-field model for a mixture of biaxial nematogens and dipolar nanoparticles - Oropesa, William G. C. [UNESP]; Nascimento, Eduardo S.; Vieira, André P. (American Physical Society (APS), 2024)
We analyze a mean-field model for mixtures involving biaxial nematogens and dipolar nanoparticles, taking into account not only orientational and isotropic pair interactions between nematogens but also orientational nematogen-nanoparticle interactions. We determine bulk equilibrium phase diagrams for a wide range of interaction strengths, identifying in each case the effect of the nanoparticles on the stability of nematic phases and on the appearance of multicritical points. Special attention is given to the limit of a low concentration of nanoparticles, in which their effect on the temperatures of both the first-order uniaxial-isotropic and the continuous biaxial-uniaxial transitions is investigated in detail.